Exploring Time-Domain Femtosecond Rotational Coherent Raman Scattering for Diagnostics - Raveesh, Meena; Hosseinnia, Ali ; 0000-0002-8358-2477; Padhiary, Abhijit; Wei, Xiangyu; Kornienko, Vassily; Kristensson, Elias; Ehn, Andreas; Peterson, Brian; Linne, Mark; Bood, Joakim (Journal of Raman Spectroscopy, 2025)
The diagnostic potential of femtosecond (fs) rotational coherent Raman scattering (RCRS) in the time domain is initially investigated. While RCRS concepts in the spectral domain obtain species selectivity and temperature sensitivity by resolving the spectral shape, mainly reflecting the Boltzmann-distributed, rotational populations of the Raman-active molecules present, the current time-domain fs-RCRS technique resolves the temporal shape of rotational revival signatures, which are influenced both by the population distributions and centrifugal distortion. Experiments in air and pure nitrogen are reported revealing temperature sensitivity in the recorded fs-RCRS temporal scans. A theoretical model can predict experimental data with good agreement for temporal scans recorded in air at room temperature and pure nitrogen at 293, 400, and 580 K. Theoretical results show that a dual-probe configuration could provide temperature sensitivity that increases with increasing temperature, that is, directly opposite to the temperature dependence of the sensitivity in spectrally resolved RCRS, which is essentially flat beyond 1500 K. This result suggests that time-domain fs-RCRS could be a useful tool for single-shot thermometry in reactive flow environments, potentially providing improved sensitivity at high temperatures compared to spectral-domain RCRS techniques. Another major benefit with the time-domain fs-RCRS technique is that it only requires a single fs laser source.
Keywords: rotational-CARS; temperature sensitivity; time-domain fs-RCRS; ultrafast diagnostics